Caracterização e análise da fragilidade ambiental da floresta nacional de Passo Fundo (Mato Castelhano, RS) - Quadros, Franciele Rosset de (Universidade Federal de São Carlos, 2014)
Considering the importance of maintenance and continuity of Conservation Units (UCs) and the adoption of strategies for biodiversity conservation in the regional landscape, this study proposes the physical environment characterization associated with the environmental fragility identification of the Passo Fundo National Forest (FLONA-PF), Mato Castelhano municipality, RS, from the perspective of identifying changes in the functions of Management Plan environmental zoning (2012). The physical environment characterization was based on the thematic maps of slope, hypsometry, geomorphology, soils, drainage network and land uses types in 2011, using a GeoEye-1 image with a spatial resolution of 0.5 m and MapInfo 8.5 and Idrisi 32 softwares for data analysis and georeferencing. It was performed a comparative analysis between land use types through 2011 and 2008, to identify the conflicts resulting from land uses changing related to the functions of the National Forest Management Plan enviromental zoning areas, subsidizing decision-making and strategies for their management. The land use classification for 2011, at a hierarchical primary level allowed to quantify and spatialize three typologies: Natural Uses, representing 42.11 % of the National Forest total area, represented by areas occupied by Araucaria Forest (FOM ) in multiple associations that are in various stages of succession and development; Anthropogenic Uses, representing 57.70% of the National Forest total area, whose original features have been modified by human activities, mainly related to araucaria (35.59 %) and Pinus (22.41 %) cultives; and, Aquatic Environments, with 0.19 % of National Forest total area. The analyzes and correlations between inventories in 2011 and 2008, for each area defined in the management plan, revealed diverse typologies in 2011 as a result of image classification methodology used in inventories than by socio- economic influences. About 283.99 ha (22.17%) of National Forest total area presents a scenario of land use conflicts, distributed among the different zones defined in the Management Plan. The use changes for each zone do not compromise the objectives and tasks set out in the Management Plan. Areas with medium environmental fragility predominated (63.22 %), followed by high fragile class (20.42 %). Areas with low fragility occupy only 15.01% of the National Forest. The classes of very low and very high fragility represent less than 1.5 % of the study area. The environmental fragility map with the inclusion of the variable Management Plan zones and the quantification of fragility classes in the areas defined in the Management Plan (2012) indicate that the proposed zoning is consistent with the needs for conservation and recovery in areas of greatest environmental fragility. Comparisons between land use types in 2008 and 2011, along with the environmental fragility to the zones defined in the Management Plan have highlighted new spatial arrangements for FLONA-PF, setting up a study of fundamental importance to reorient meet the goals of the management plan, in addition to supporting environmental planning actions of the regional landscape.
Environmental characterization and fragility of Passo Fundo National Forest (Mato Castelhano, RS)
Keywords: Conservação; Unidades de conservação; Plano de manejo; Análise multicritério; Gestão ambiental; Paisagem; Conservation unit; Management plan; Multicriteria analysis; Environmental management; Landscape; CIENCIAS BIOLOGICAS::ECOLOGIA